Clinical Presentations and Outcomes of Children in Canada With Recurrent Invasive Pneumococcal Disease From the IMPACT Surveillance Network. Issue 4 (4th March 2022) - Murad, Yousif; Hung, Te-Yu; Sadarangani, Manish; Morris, Shaun K.; Le Saux, Nicole; Vanderkooi, Otto G.; Kellner, James D.; Tyrrell, Gregory J.; Martin, Irene; Demczuk, Walter; Halperin, Scott A.; Bettinger, Julie A.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Invasive pneumococcal disease due to Streptococcus pneumoniae can cause mortality and severe morbidity due to sepsis, meningitis and pneumonia, particularly in young children and the elderly. Recurrent invasive pneumococcal disease is rare yet serious sequelae of invasive pneumococcal disease that is associated with the immunocompromised and leads to a high mortality rate. Method: This retrospective study reviewed recurrent invasive pneumococcal disease cases from the Canadian Immunization Monitoring Program, ACTive (IMPACT) between 1991 and 2019, an active network for surveillance of vaccine-preventable diseases and adverse events following immunization for children ages 0–16 years. Data were collected from 12 pediatric tertiary care hospitals across all 3 eras of public pneumococcal conjugate vaccine implementation in Canada. Results: The survival rate within our cohort of 180 recurrent invasive pneumococcal disease cases was 98.3%. A decrease of 26.4% in recurrent invasive pneumococcal disease due to vaccine serotypes was observed with pneumococcal vaccine introduction. There was also a 69.0% increase in the rate of vaccination in children with preexisting medical conditions compared with their healthy peers. Conclusion: The decrease in recurrent invasive pneumococcal disease due to vaccine-covered serotypes has been offset by an increase of non-vaccine serotypes in this sample of Canadian children.